Soviet aims in Southern Africa: Economic considerations - Meyer, C.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
While much has been said about the increasing involvement of the USSR in Southern Africa, little has been said about how and why the USSR wishes to achieve its aims in the sub-continent. Little has really changed since 1917, when Lenin himself declared bluntly that the scientific concept of dictatorship means neither more nor less than unlimited power, resting directly on force, not limited by anything, nor restricted by any laws, nor any absolute rules. Nothing else but that.